PENGEMBANGAN SISTEM INFORMASI RESERVASI HOMEYKU DI KALIURANG BERBASIS WEBSITE MENGGUNAKAN METODE WATERFALL - Arnika Fitria Diah Utami; Muhammad Ridwan; Abdul Khakim; Ervira Diva Grafvera (The Indonesian Journal of Computer Science Research, 2023)
The aim of this research is to develop a Web-based Homeyku Reservation Information System in Kaliurang using the Waterfall method. This system is designed to provide users with an efficient and easy-to-use reservation experience. The Waterfall method is used in the development of this system, which involves the stages of requirements analysis, system design, implementation, testing and maintenance. Requirements analysis is carried out to identify user requirements and system technical requirements. The system design includes the appearance of the user interface, database structure and business logic. The implementation phase involves building a website-based system using the appropriate technology and programming language. Tests are carried out to ensure the system works properly and according to requirements. The maintenance phase is conducted to periodically monitor the system, address issues, and upgrade features if needed. By implementing the Waterfall method, it is hoped that the Homeyku reservation information system in Kaliurang can provide a satisfying reservation experience for users and make it easier for managers to manage the reservation process.